Avaliação da assistência estudantil em relação ao reconhecimento das diversidades no Campus Agrícola de Umirim/CE - Brandão, Lorena de Menezes (2017)
The present study aims to evaluate the Student Assistance and the diversity of gender, ethnic-racial and sexual in the agricultural campus of Umirim/CE in facing the associated forms of inequality and exclusion. Student assistance is defined as a social policy inserted in the policy of higher and professional education, in which we define its analysis in a campus of the Federal Institute of Education, Science and Technology of Ceará - IFCE. For the purpose of this study, we problematize the contradictions inherent in the process of capital reorganization whose interests of the world financial organisms orient the states of the peripheral countries, with a cut for Brazil, whose educational reforms aim to meet the demands of internationalized capital, repercussions on the reorganization of markets and in the dramatic inequalities expressed in social relations. From this context we seek to unveil the possibilities of student assistance in building a more equitable society for the different segments of society inserted in education policy. The research carried out is of quanti-quali nature, based on the methodology of the in-depth evaluation (RODRIGUES 2008, 2011, 2017) which considers as analysis dimensions the content of the policy; the analysis of the context in which it was formulated; its institutional trajectory and its temporal and territorial spectrum. Bibliographic and documentary research was based on the interaction of the theoretical discussion of the authors and the categories of analysis, with the documents and norms on the subject, plus the data collected with the field research. We highlight as the main conclusions of this evaluation the need to overcome the vision of an student assistance based on the "bolsification" and assistance of student demands, expanding its performance to other dimensions of the subjects' lives. It is necessary to strengthen the understanding that student assistance is an educational policy, with the important role of contributing to the formative processes of young people, enhancing their human, cultural, social and political development. In this sense, it is inserted directly into the expressions of social, material and symbolic inequalities, demanding qualified responses, which need to be articulated and integrated with other social policies, as well as with other institutional segments in the space where it is operationalized.